2022
DOI: 10.3390/su14127224
|View full text |Cite
|
Sign up to set email alerts
|

Performance of E-Banking and the Mediating Effect of Customer Satisfaction: A Structural Equation Model Approach

Abstract: Online payment is a trend that is gaining momentum globally. As a result of digitisation, the advent of online banking has increasingly made its way into the modern marketplace, serving not only customers but also corporations. The primary data were gathered from 287 participants. Stratified random sampling was used. Structure Equation Modelling (SEM), reliability, convergent, discriminate validity and model fitness were achieved through SmartPLS 3 (Christian M. Ringle, Germany). The findings reveal that effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 54 publications
(55 reference statements)
1
4
0
Order By: Relevance
“…Further, SAT was shown to have the greatest impact on CUI, with a path coefficient of 0.540 and significance at the 0.001 level. HB is a powerful predictor of future behavior; this was in line with previous research that found a link between the use of technology and greater academic achievement (Arshad Khan & Alhumoudi, 2022;Hwang et al, 2022).…”
Section: Structural Modelsupporting
confidence: 89%
See 1 more Smart Citation
“…Further, SAT was shown to have the greatest impact on CUI, with a path coefficient of 0.540 and significance at the 0.001 level. HB is a powerful predictor of future behavior; this was in line with previous research that found a link between the use of technology and greater academic achievement (Arshad Khan & Alhumoudi, 2022;Hwang et al, 2022).…”
Section: Structural Modelsupporting
confidence: 89%
“…When students perceive m-learning systems as effective, user-friendly, and equipped with high-quality communication tools, they are more likely to feel satisfied with their learning experiences. This satisfaction, in turn, reinforces their intention to continue using the technology (Arshad Khan & Alhumoudi, 2022;Hwang et al, 2022). By integrating this mediating role into the research framework, this study aims to shed light on the intricate dynamics between students' perceptions, satisfaction, and their determination to persist in utilizing m-learning solutions within the unique context of Iraqi universities facing an unstable environment.…”
Section: Mediating Role Of Satisfactionmentioning
confidence: 98%
“…While there are instances where authors treated service quality as a unidimensional construct [59], it is more commonly measured multidimensionally [56,58,60]. As shown in Table 1, the most frequently reported measures include privacy and security, efficiency, responsiveness, assurance (trust), ease of use, and others [48].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Vijayanand and Kumar (2021) conducted an empirical study to analyze the impact of SQ on satisfaction in e-banking services in public sector banks in India, for a simple random sample of (667) clients and concluded that the various e-banking factors (Responsiveness, Convenience, and Security) and demographic variables have a positive correlation on CS. Khan and Alhumoudi (2022) presented the structural equation model approach, using CS as a mediator to measure the performance of e-banking services for a stratified random sample. As a result, efficiency, reliability, and service quality are a direct influence on CS and retention.…”
Section: Introductionmentioning
confidence: 99%